ANALISIS SALES FORECASTING KENDARAAN MOBIL LISTRIK MODEL BATTERY ELECTRIC VEHICLE DI INDONESIA (METODE LEAST SQUARE) - Nadira Zahra; Aldi Akbar (Institut Pendidikan Tapanuli Selatan, 2024)
Battery electric vehicles (BEVs) are one of the most environmentally friendly and low-emission forms of transportation that can help reduce greenhouse gas (GHG) emissions. The use of alternative transportation is a step that can help support the 13th goal of sustainable development goals (SDGs) related to climate change. However, based on data released by the official association GAIKINDO (Gabungan Industri Kendaraan Bermotor Indonesia), wholesales of electric cars only account for about 1.35% of the overall automotive market share in Indonesia. Therefore, this study discusses sales forecasting for each brand that produces battery-based electric car vehicles and has wholesales recorded at GAIKINDO for the period January 2021 - September 2023. The purpose of this study is to determine the sales projection and reliability of the forecasting model for each brand using the least square method. This research method is quantitative with descriptive research type through F test hypothesis testing. Based on the results of the discussion of the eleven brands studied, it is found that the sales forecasting models for the Hyundai, DFSK, Lexus, Toyota, Mini, and Wuling brands are considered feasible and reliable enough to be used, while the sales forecasting models for the Nissan, KIA, Mercedes-Benz, Morris Garage, and BMW brands are considered not feasible and reliable enough.